Kant and the platypus: essays on language and cognition - "Eco,Umberto" (London, 2000)
How much do our perceptions of things depend on our cognitive ability, and how much on our linguistic resources? Where, and how, do these two questions meet? Umberto Eco undertakes a series of idiosyncratic and typically brilliant explorations, starting from the perceived data of common sense, from which flow an abundance of 'stories' or fables, often with animals as protagonists, to expound a clear critique of Kant, Heidegger and Peirce. And as a beast designed specifically to throw spanners in the works of cognitive theory, the duckbilled platypus naturally takes centre stage.
Keywords: Perception